The effect of cytokines produced by human adipose tissue on monocyte adhesion to the endothelium - Cejkova, Sona; Kubatova, Hana; Thieme, Filip; Janousek, Libor; Fronek, Jiri; Poledne, Rudolf; Kralova Lesna, Ivana (Cell adhesion & migration, 2019)
Visceral adipose tissue (VAT) may play a critical role in atherosclerotic cardiovascular disease. The goal of this study was to determine the effect of human VAT-released pro‑inflammatory cytokines on monocyte adhesion to the endothelium. The cytokine effects on monocyte adhesion to the endothelial cells (ECs) were tested using adipose tissue-conditioned media (ATCM) prepared by culturing human VAT. The cytokines concentrations in ATCM, the cytokines expression and adhesion molecules in stimulated ECs were measured. The concentrations of IL-1β,TNF-α,MCP-1,IL-10,and RANTES measured in ATCM correlated positively with monocyte adhesiveness to ECs. Additionally, ATCM increased the adhesion molecules (ICAM-1, VCAM-1) gene expression. Selective inhibitors highlighted the importance of IL-1β and TNF-α in the process by a significant decrease in monocyte adhesion compared to ATCM preconditioning without inhibitors. Human VAT significantly increased monocyte adhesion to ECs. It was significantly influenced by IL-1β, TNF-α, MCP-1, IL-10, and RANTES, with IL-1β and TNF‑α having the strongest impact.
Keywords: Humans; Endothelium, Vascular; lidé středního věku; cévní endotel; Intra-Abdominal Fat; cytokiny; inflammation; dospělí; ateroskleróza; Cell Adhesion; lidé; Cells, Cultured; adipose tissue; Adult; nitrobřišní tuk; mezibuněčná adhezivní molekula-1; Endothelial Cells; Vascular Cell Adhesion Molecule-1; Atherosclerosis; Middle Aged; cytokines; kultivované buňky; Cytokines; endoteliální buňky; Monocytes; cévní buněčněadhezivní molekula-1; monocyty; buněčná adheze; Intercellular Adhesion Molecule-1; endothelium; Culture Media, Conditioned; kultivační média speciální